Analisis Proses Pembuatan Tujuan Pembelajaran Berdasarkan Capaian Pembelajaran pada Siswa Kelas IV SDN Pondok Jengkol - Magdalena, Ina; Elyipuspita, Melina; Irmawati, Nabila (Lembaga Yasin AlSys, 2023)
Learning activities are the core of the educational process. Learning activities and the preparation of learning tools have changed along with the change in curriculum from K-13 to Merdeka Curriculum. In the independent curriculum, Basic Competencies are updated to competency achievements which are written from several paragraph sentences. Indicators are also updated to Learning Objectives. The independent curriculum has three phases related to Learning Outcomes. In grade IV elementary school, it enters phase B in the Learning Outcomes. The method used in this research is descriptive qualitative method with data collection through observation and interviewing one of the fourthgrade teachers. The results of the study state the difficulty of teachers in formulating Learning Objectives and teachers have difficulty in analyzing whether or not the available assessment assessments are in accordance with all teaching and learning activities in the classroom.